Mate-searching behaviour and sex pheromones in Branchinecta lindahli Packard, 1883 (Branchiopoda: Anostraca). Issue 1 (2nd February 2019) - Rogers, D Christopher
Abstract: Anostracans (Branchiopoda, Anostraca) have some of the most elaborate mating behaviours among crustaceans. Behaviour of adult anostracans was observed and quantified in 1) receptive males and females, 2) unreceptive females, and 3) isolated individuals of both sexes of Branchinecta lindahli Packard, 1883 . Males demonstrated specific mate-searching behaviours, cruising in the lower water column around salient objects. Receptive females hovered around the same objects high in the water column, allowing males to approach from below. Unreceptive females as well as males never exposed to females tended to stay low in the water column and moved around little. Males entirely isolated from females immediately began searching behaviours when water from female cultures was added, demonstrating the presence of pheromones.